Meningiomas in children and adolescents: a meta-analysis of individual patient data - Kotecha, Rishi S; Pascoe, Elaine M; Rushing, Elisabeth J; Rorke-Adams, Lucy B; Zwerdling, Ted; Gao, Xing; Li, Xin; Greene, Stephanie; Amirjamshidi, Abbas; Kim, Seung-Ki; Lima, Marco A; Hung, Po-Cheng; et al. (The lancet oncology, 2011)
The epidemiological, prognostic, and therapeutic features of child and adolescent meningioma are poorly defined. Clinical knowledge has been drawn from small case series and extrapolation from adult studies. This study was done to pool and analyse the clinical evidence on child and adolescent meningioma. Searches of PubMed, Medline, and Embase identified 35 case series of child and adolescent meningioma completed over the past 21 years. Individual patient data were obtained from 30 studies via direct communication with investigators. Primary outcomes were relapse-free survival (RFS) and overall survival. Prognostic variables were extent of initial surgery, use of upfront radiotherapy, age, sex, presence of neurofibromatosis, tumour location, and tumour grade. RFS and overall survival were analysed using Kaplan-Meier survival curves and multivariable Cox regression models. From a total of 677 children and adolescents with meningioma, 518 were eligible for RFS analysis and 547 for overall survival analysis. Multivariable analysis showed that patients who underwent initial gross-total resection had better RFS (hazard ratio 0·16, 95% CI 0·10–0·25; p<0·0001) and overall survival (0·21, 0·11–0·39; p<0·0001) than those who had subtotal resection. No significant benefit was seen for upfront radiotherapy in terms of RFS (0·59, 0·30–1·16; p=0·128) or overall survival (1·10, 0·53–2·28; p=0·791). Patients with neurofibromatosis type 2 (NF2) had worse RFS than those without neurofibromatosis (2·36, 1·23–4·51; p=0·010). There was a significant change in overall survival with time between patients with NF2 compared with those without neurofibromatosis (1·45, 1·09–1·92; p=0·011); although overall survival was initially better for patients with NF2 than for those without neurofibromatosis, overall survival at 10 years was worse for patients with NF2. Patients with WHO grade III tumours had worse RFS than those with WHO grade I (3·90, 2·10–7·26; p<0·0001) and grade II tumours (2·49, 1·11–5·56; p=0·027). Extent of initial surgical resection is the strongest independent prognostic factor for child and adolescent meningioma. No benefit for upfront radiotherapy was noted. Hence, aggressive surgical management, to achieve gross-total resection, is the initial treatment of choice. In the event of a subtotal resection, repeat resection is recommended to achieve maximum extirpation. Close observation is warranted for patients who have a subtotal resection or who have WHO grade III tumours. Patients without neurofibromatosis should have a minimum 10-year follow-up, whereas patients with NF2 should be considered a special risk category, necessitating life-long follow-up. None.